Effects of Switching From Calcium Carbonate to Lanthanum Carbonate on Bone Mineral Metabolism in Hemodialysis Patients. (16th April 2013) - Manabe, Rie; Fukami, Kei; Ando, Ryotaro; Sakai, Kazuko; Kusumoto, Takuo; Hazama, Takuma; Adachi, Takeki; Kaida, Yusuke; Nakayama, Yosuke; Ueda, Seiji; Kohno, Keisuke; Wada, Yoshifumi; et al.
Abstract: Phosphate binders are useful for the treatment of hyperphosphatemia in hemodialysis (HD) patients. This study was performed to examine the effects of switching from calcium carbonate (CC) to lanthanum carbonate (LC) on bone mineral metabolism and inflammatory markers in HD patients. We conducted 29 stable HD patients receiving CC, which was replaced by LC and followed‐up for 12 weeks. Patients underwent determinants of blood chemistries such as serum calcium (Ca), phosphorus, parathyroid hormone (PTH) and vitamin D status, and interleukin‐6 (IL‐6) mRNA levels in whole blood cells were evaluated by real‐time PCR just before and after the treatment with LC. Corrected levels were significantly reduced, but serum phosphorus levels (P levels) were unchanged after LC treatment. Switching to LC increased whole‐PTH, osteocalcin, 1, 25(OH)2 D3 levels and 1, 25(OH)2 D3 /25(OH)D3 ratio. 1, 25(OH)2 D3 /25(OH)D3 ratio was negatively correlated with HD duration. Furthermore, whole blood cell IL‐6 mRNA levels were significantly reduced by LC treatment. We provided that the switching from CC to LC improved Ca overload and ameliorated vitamin D and inflammatory status in HD patients. These observations suggest that LC may play a protective role for the progression of atherosclerosis and vascular calcification in these patients.